Clinicopathologically problematic melanocytic tumors: a case-based review - Zoe Apalla; Christina Nikolaidou; Aimilios Lallas; Elena Sotiriou; Elizabeth Lazaridou; Ioannis Venizelos; Mattheos Bobos; Efstratios Vakirlis; Demetrios Ioannides; Gerardo Ferrara (Mattioli1885, 2018)
Background: In spite of recent advances in the histopathological and molecular diagnosis of melanocytic neoplasms, a certain proportion of these lesions remain a daunting challenge for both the clinician and the pathologist. Objectives: To emphasize the importance of close collaboration between the clinicians and the pathologists in case of problematic melanocytic lesions, Patients: We report and discuss 5 problematic scenarios of melanocytic lesions, including tumoral melanosis, nevoid melanoma, lentiginous melanoma, spitzoid melanoma and BAPoma that may pose diagnostic difficulties in our practice. Conclusions: Clinico-dermoscopic-pathological correlation, with incorporation of all the available data, in problematic melanocytic skin neoplasms is of paramount importance for accurate diagnosis.